Investment timing with regime switching - Elliott, Robert J., author; Miao, Hong, author; Yu, Jin, author; International Journal of Theoretical and Applied Finance, publisher (Colorado State University. Libraries, 2008)
We investigate the optimal investment timing strategy in a real option framework. Depending on the state of the economy, whose changes are modeled by a Markov chain, the investment cost can take one of two values. The optimal investment timing decision is determined by finding the free boundary of a perpetual American option. Three investment timing policies, based on different assumptions of investors' information sets, are determined and compared. In the full information case, a significantly earlier optimal exercising time is indicated. We show that an optimal-timing policy suggested by the conventional real option model might ruin the investment opportunities.
Published as: International Journal of Theoretical and Applied Finance, vol. 12, no. 4, pp. 443-463, 2009, https://doi.org/10.1142/S0219024909005361.
Keywords: regime switching; real option; investment timing